442 UTEROPLACENTAL INSUFFICIENCY CAUSES CHANGES IN LEPTIN RECEPTOR EXPRESSION IN THE INTRAUTERINE GROWTH RETARDED RAT BRAIN. Issue 1 (1st January 2007) - O'Grady, S. P.; Caprau, D. M.; Moyer-Mileur, L.; Hale, M. A.; Ke, X.; Yu, X.; Men, P.; Callaway, C. W.; McKnight, R. A.; Lane, R. H.
Abstract : Background: Uteroplacental insufficiency causes intrauterine growth retardation (IUGR). IUGR has been linked to a variety of metabolic and developmental disorders, including diabetes, obesity, infertility, stunted skeletal growth, and impaired brain growth. Such disorders may be mediated through the direct affect of IUGR on cerebral proteins and receptors involved in reproductive and metabolic pathways. Leptin and ghrelin have been linked to energy homeostasis, reproductive development, and neuronal synthesis, but the expression of leptin and ghrelin receptors (Ob-Rb and GHS-R, respectively) in the whole brain of IUGR rat pups is unknown. Additionally, the effect of IUGR on kisspeptin (KiSS-1), a protein regulated by leptin and recently implicated in development of the reproductive axis, is unknown. Objectives: We hypothesized that uteroplacental insufficiency would cause increased expression of Ob-Rb and GHS-R and decreased expression of KiSS-1 in the whole brain of IUGR rats. Methods: To test this, we measured expression of Ob-Rb, GHS-R, and KiSS-1 in the whole brain of IUGR pups obtained by bilateral uterine artery ligation. Sham surgeries were used as controls. Brains were harvested and flash frozen. Real-time RT-PCR was used to measure mRNA expression on day 0 (D0) and day 21 (D21) of life. Results: Although there was no significant difference between IUGR and SHAM rats in GHS-R or KiSS-1 expression, D0 IUGR pups had significantly higher expression of Ob-Rb mRNA in whole brain than D0 SHAM pups ( p = .003). Preliminary results indicate a trend toward decreased expression of Ob-Rb mRNA in whole brain of D21 IUGR rats ( p = .09). Conclusion: We conclude that uteroplacental insufficiency up-regulates Ob-Rb expression at D0 in the IUGR rat brain. We have shown that the IUGR insult epigenetically regulates cerebral gene expression, and we speculate that Ob-Rb expression may be modulated through changes in chromatin structure. Additionally, recent research has demonstrated that leptin signaling affects adrenal glucocorticoid production as well as CNS glucocorticoid receptor expression. We have previously shown that IUGR affects glucocorticoid receptor expression in the rat brain, and we postulate that this effect may be mediated through up-regulation of cerebral Ob-Rb receptors.